Qia’erdunbasixi Fe–Cu Deposit in Sawur, Xinjiang: A Case Study of Skarn Deposit Hosted by Volcanic Rock - Yang, Shuang; Zhou, Qiu-Shi; Wang, Rui; Zhu, Yongfeng (Frontiers in Earth Science, 2022)
The Sawur Cu–Au belt, northern Xinjiang, China, is the eastward extension of the Zarma–Sawur Cu–Au belt in Kazakhstan, where Late Paleozoic volcanic rocks and intrusions are highly developed. The Qia’erdunbasixi Fe–Cu deposit in Sawur is a recently discovered deposit and is still under exploration. The intrusive rocks are syenite and diorite, and the wall rocks consist of andesite and minor basalt, lamprophyre, and tuff. The U–Pb SHRIMP zircon age of the Qia’erdunbasixi syenite intruding into the volcanic rocks is 345 ± 2.2 Ma (MSWD = 1.3), presenting as the lower limit of skarn Fe mineralization. The intrusives belong to the calc–alkaline to high-K calc-alkaline series with large ion lithophile element (LILE) enrichment, high LREE/HREE fractionation, and high field strength element (HFSE) depletion. The initial 87Sr/86Sr ratios of the Qia’erdunbasixi syenite range from 0.70403 to 0.70420, and the εNd(t) values are from +5.5 to +6.8, which are the typical characteristics of island arc igneous rocks. Diorites having similar REE features with syenite should share the same magma source. Magnetite and copper mineralization develop mostly along the contact zones of syenite and diorite, respectively. Fe mineralization develops along the contact zone of syenite, with typical skarn zonation. The metallogenesis event can be divided into the prograde skarn stage (diopside–augite–andradite–magnetite–calcite–quartz), retrograde skarn stage (epidote–chlorite–actinolite–K-feldspar–calcite–magnetite–quartz), and quartz–sulfide stage (quartz–magnetite–K-feldspar–calcite–sercite–chlorite–actinolite–prehnite–chalcopyrite–pyrite). The early–mid-stage magnetite with certain amounts of Ti and V was crystallized from magma, while the late-stage magnetite has the typical characteristics of hydrothermal calcic skarn magnetite. The temperature of mineralization is between 350 and 450°C based on mineral assemblages and phase diagrams. Copper mineralization is concentrated along the outer contact zone of the diorite. Paragenesis sequences of the four stages of mineralization could be identified for copper mineralization: 1) albite–quartz; 2) chalcopyrite–pyrite–gold–seriate–quartz; 3) chalcopyrite–pyrite–epidotic–reunite; and 4) sphalerite–galena–quartz–calcite. Qia’erdunbasixi is a composite deposit with skarn-type Fe mineralization and mesothermal Cu mineralization and has a genetic relationship with magmatism in an island arc setting.